2018
DOI: 10.1097/scs.0000000000004326
|View full text |Cite
|
Sign up to set email alerts
|

Retracted or Withdrawn Publications in Journals Relating to Plastic Surgery

Abstract: The aim of this study was to determine how many papers have been retracted or withdrawn, and for what reason, in journals relating to plastic surgery.PubMed and SCOPUS were used, with the search terms (retracted OR withdrawn) AND (article OR publication OR paper) AND {(plastic surgery) OR (cosmetic surgery) OR (maxillofacial surgery) OR (craniofacial surgery)}. The papers were analyzed and classified according to the reason for retraction or withdrawal, journal name, publication year, and author. In the PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…of fellow trainees in gynaecological oncology, over 70% reported non‐compliance with research practices, including IRB processes, authorship assignment, and compliant data storage . Similarly, in a study of gynaecological oncology fellowship applicants reporting publications on their curriculum vitae, approximately one‐third of the applicants had at least one publication that could not be confirmed . Although pressures do exist to be academically productive, there are regulations and rules in place that, when followed, can help researchers publish high‐quality, valid scientific work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of fellow trainees in gynaecological oncology, over 70% reported non‐compliance with research practices, including IRB processes, authorship assignment, and compliant data storage . Similarly, in a study of gynaecological oncology fellowship applicants reporting publications on their curriculum vitae, approximately one‐third of the applicants had at least one publication that could not be confirmed . Although pressures do exist to be academically productive, there are regulations and rules in place that, when followed, can help researchers publish high‐quality, valid scientific work.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, in a study of gynaecological oncology fellowship applicants reporting publications on their curriculum vitae, approximately one-third of the applicants had at least one publication that could not be confirmed. 19 Although pressures do exist to be academically productive, there are regulations and rules in place that, when followed, can help researchers publish high-quality, valid scientific work. It is important for all clinician scientists to be aware that article retraction can have serious consequences within the medical community, for patient care, scientific advancement, and career advancement.…”
Section: Discussionmentioning
confidence: 99%
“…9 Plastic surgery is not immune to these practices either, as plagiarism, dual publication, and retraction based on falsified claims and invalid research methods have been reported. 30,31 These are also clearly unethical and undermine research integrity but are much less publicized. It begs the question whether there is a hierarchy of misconduct?…”
Section: Fraud Fabrication and Plagiarismmentioning
confidence: 99%
“…In the postpublication phase, it is encouraging that journals rarely have to issue retractions or withdrawals of published works, which are mainly due to duplication, plagiarism, lack of permission, or at the author's request. 5…”
mentioning
confidence: 99%
“…In the postpublication phase, it is encouraging that journals rarely have to issue retractions or withdrawals of published works, which are mainly due to duplication, plagiarism, lack of permission, or at the author's request. 5 Although technology has been slow to disrupt medicine other than at the periphery, it has come to the aid of journal editorial teams in the form of plagiarism and duplicate publication detection software. Regrettably this software can do little to protect against data fabrication and falsification.…”
mentioning
confidence: 99%